2023
DOI: 10.21203/rs.3.rs-2827753/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-depth analysis benefital effect of probiotics and fatty acids in anesis of depression

Abstract: Depression is the most prevalent presenting psychiatric symptom among individuals of all ages and backgrounds, affecting approximately 300 million people worldwide. Therefore, it deserves a great deal of attention when it comes to management. An increasing body of evidence reveals that probiotics and fatty acids can improve with depression. However, the viewpoint claims that there is no effect on depression. Network meta-analyses of existing datasets provide for the estimation of comparative efficacy, the summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…3 out of the 10 first traits were not directly brain-related: heel bone mineral density (HBMD) (144 regions), total BMD (125 regions), and height (113 regions). The associations between BMD and the brain have been investigated in the context of neurological disorders [29,30,54], as well as in samples of healthy subjects [2]. Loskutova et al [29,30] reported a correlation between BMD and an early onset of Alzheimer's disease (AD), as well as with several brain volumes.…”
Section: Gwas Catalog Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 out of the 10 first traits were not directly brain-related: heel bone mineral density (HBMD) (144 regions), total BMD (125 regions), and height (113 regions). The associations between BMD and the brain have been investigated in the context of neurological disorders [29,30,54], as well as in samples of healthy subjects [2]. Loskutova et al [29,30] reported a correlation between BMD and an early onset of Alzheimer's disease (AD), as well as with several brain volumes.…”
Section: Gwas Catalog Associationsmentioning
confidence: 99%
“…HBMD is postulated to be a causal factor for multiple sclerosis (MS) through an increased risk of fractures [54]. Bae et al [2] showed that osteoporosis increases the pace of parenchymal atrophy and ventricular enlargement during aging of healthy individuals.…”
Section: Gwas Catalog Associationsmentioning
confidence: 99%